USMLE step 2 secrets - Brochert, Adam (Hanley & Belfus, 2004)
Written by Dr. Brochert, who scored in the 99th percentile in Steps 1 and 2 of the U.S. Medical Licensing Exam (USMLE), this new addition to The Secrets Series(r) provides essential questions and answers covering topics that have appeared on recent Step II * Coverage of all specialty and subspecialty topics covered on Step 2 * All the most important "need-to-know" questions-and-answers in the proven format of the highly acclaimed Secrets Series(r) * Concise answers that include the author's pearls, tips, memory aids, and "secrets" * Bulleted lists, algorithms, and illustrations for quick review * Thorough, highly detailed index * Thought-provoking questions that provide succinct answers * Presentation of a vast amount of information, but not overly simplistic